Analysis of the influece of ungulates on the regeneration of Dinaric fir-beech forests in the research site Trnovec in the Kočevje forest managementregion - Jarni, Kristjan (Zbornik gozdarstva in lesarstva, 2004)
In the period 1970-2000, 152 fenced-in areas were built in the Kočevje Forest Management Region with an aim to protect tree seedlings and saplings from ungulatesć activity and to monitor the influence of roe and red deer on natural regeneration. The average surface area of fenced areas is 0.71 ha. Using the pair comparison technique (fenced vs. unfenced areas), the structureand the composition of the natural regeneration of tree species as well as complete shrub and herb vegetation were analysed in the research site Trnovec. Furthermore, the vegetation was investigated using the Braun-Blanquetmethod. The research results show significant differences between fenced and unfenced areas, both in tree species composition and in theheight structure of the sapling community. In fenced areas the total numberof saplings taller than 50 cm is higher and an increase is also evident in the number of saplings of silver fir Abies alba, sycamore Acer pseudoplatanus, elm Ulmus glabra and other minor tree species. There are also significant differences in species composition and in the abundance of plant species in the herb layer. The results show that natural regeneration of Dinaric fir-beech forests is successful, provided the influence of ungulates is excluded.
Keywords: bukev; jelenjad; jelka; jelovo-bukovi gozdovi; srnjad